Novel experimental setup for time-of-flight mass spectrometry ion detection in collisions of anionic species with neutral gas-phase molecular targets - Oller, J. C. (2018)
PLV acknowledges the Portuguese Foundation for Science and Technology (FCT-MEC) through SFRH/BSAB/105792/ 2014 during his sabbatical stay at CSIC, Madrid and the research grants PTDC/FIS-ATO/1832/2012 and UID/FIS/00068/ 2013. FFS acknowledges FCT-MEC through researcher grant IF-FCT IF/00380/2014. We also acknowledge the Spanish Ministerio de Economía y Competitividad (Project No. FIS 2012-31230). Some of this work forms part of the EU/ESF COST Actions CM1401 and CM1301, Our Astro-Chemical History and Chemistry for Electron-Induced Nanofabrication, respectively. LE-G and GG acknowledge the FP7-PEOPLE-2013-ITN research grant “Advanced Radiotherapy, Generated by Exploiting Nanoprocesses and Technologies (ARGENT)”.